2016
DOI: 10.1136/heartjnl-2015-308467
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging to identify susceptibility for ventricular arrhythmias in ischaemic left ventricular dysfunction

Abstract: Of all previously validated approaches to evaluate the arrhythmic substrate, global impaired hyperaemic MBF was the only independent predictor of VA inducibility. Moreover, a combined approach of different imaging variables did not have incremental value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is in this context that the current study by Rijnierse et al 8 may be of particular clinical importance. The authors have combined several state of the art methods in order to take advantage from latest non-invasive imaging techniques covering most of the above-mentioned areas of research with a potential for improved risk stratification before ICD implantation.…”
mentioning
confidence: 75%
“…It is in this context that the current study by Rijnierse et al 8 may be of particular clinical importance. The authors have combined several state of the art methods in order to take advantage from latest non-invasive imaging techniques covering most of the above-mentioned areas of research with a potential for improved risk stratification before ICD implantation.…”
mentioning
confidence: 75%
“…Further studies have confirmed the importance of total denervated myocardium volume in predicting VA in patients with ischemic cardiomyopathy and reduced systolic function [96]. In a similar patient demographic as PAREPET, patients with newly placed ICDs and inducible VA during an EPS had larger denervation areas as assessed with [ 11 C]-HED compared to non-inducible patients.…”
Section: Predicting Ventricular Arrhythmias and Sudden Cardiac Death mentioning
confidence: 92%
“…In contrast to preclinical studies, clinical studies have shown that the total denervation area assessed with PET [ 11 C]-HED was more important in predicting ventricular arrhythmias (VA) [51••, 96] and SCD [51••] than the innervation/perfusion mismatch area and the area of denervated but viable myocardium. In the PAREPET (Prediction of Arrhythmic Events with Positron Emission Tomography) study, a relatively larger group of patients ( n = 204) with ischemic cardiomyopathy that were eligible to receive a primary prevention ICD (LVEF <35%) underwent complementary PET imaging of resting flow ([ 13 N]-ammonia), myocardial viability (insulin-stimulated ([ 18 F]-FDG), and sympathetic innervation ([ 11 C]-HED) at baseline [51••].…”
Section: Predicting Ventricular Arrhythmias and Sudden Cardiac Death mentioning
confidence: 99%
“…The assessment of infarct scar is important also to risk stratify patients according to their risk of arrhythmic events, as it is well known that myocardial scar represents the substrate for re-entrant arrhythmias [ 73 ]. Different studies on patients undergoing CMR prior to ICD implantation have shown that scar extent is stronger than LVEF in predicting arrhythmic events (sudden death, ICD discharge, ventricular arrhythmias) and inducibility at electrophysiologic study (EPS) [ 74 76 ] and remains the strongest predictor, also in patients with preserved ejection fraction [ 77 ]. Scar analysis on CMR is based on different signal intensity of the infarcted area as compared to an area of normal, remote myocardium.…”
Section: Risk Stratificationmentioning
confidence: 99%